IMPLEMENTASI ORACLE SPATIAL UNTUK PEMETAAN KETAHANAN DAN KERAWANAN PANGAN DI KABUPATEN BREBES - Agusta Praba Ristadi Pinem (Jurusan Teknologi Informasi Universitas Semarang, 2016)
Food insecurity is a common problem in some areas and it must be taken into consideration for its involvement into human life. Food insecurity refers to the inability of people in local communities to secure adequate food. Food insecurity maps can be used to identify areas that tend to insecure. Based on Central Java Food Security and Vulnerability Atlas (FSVA) in 2010, Brebes has been in a food secure status and it makes difference from all districts and cities in Central Java province. The anomaly on food security status in Brebes is the main concern on this research by implementing Oracle Spatial to mapping the food security and vulnerability. Oracle Spatial combines the spatial data and food data for displaying information about food security status within each district in Brebes.